SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK BINAKARYA MANDIRI BEKASI - Mely Mailasari; Linda Marlinda; Ahmad Setiadi (Jurnal Sistem Informasi, 2014)
Abstract— Academic activities is a process which does educational activities whose activities require information quickly. However faktanya ada several problems that occurred. This is because there is often a buildup of student data and student data made it difficult to search the data when it is needed, it takes quite a long time in the making student data report, recording students' academic grades into the book value of a student's academic as well as into the report cards and also create a report that a student's academic value must be submitted to the principal, time constraints of parents so that information about the academic is not obtained quickly, through this study is expected to build a computer-based academic information system that can minimize deficiencies that occur so as to meet the needs of information for teachers, students up to the public wide.